Orthodontic Pre Grafting Closure of Large Alveolar Bony and Soft Tissue Gaps: A Novel Nonsurgical Protraction of the Lesser Segments in Growing Patients With Cleft Lip and Palate. (March 2022) - Meazzini, Maria Costanza; Cohen, Noah; Battista, Valeria Marinella Augusta; Incorvati, Cristina; Biglioli, Federico; Autelitano, Luca
Background: Closure of wide alveolar clefts with large soft tissue gaps and reconstruction of the dentoalveolar defect are challenging for the surgeon. Some authors successfully used interdental segmental distraction, which requires an additional surgical procedure. Objective: This study evaluates the effectiveness of tooth borne devices utilized to orthopedically advance the lesser segments, with a complete approximation of the soft tissue of the alveolar stumps, allowing traditional simultaneous soft tissue closure and bone grafting, and avoiding the need for supplementary surgery. Methods: Eight growing patients, 2 with unilateral complete cleft lip and palate (UCLP) and 6 with bilateral complete cleft lip and palate (BCLP), with large soft tissue and bony alveolar defects prior to bone grafting were prospectively selected. A banded rapid palatal expander (RPE) in BCLP and a modified RPE in UCLP combined with protraction face mask in younger patients or a modified Alt-Ramec in patients older than 12 years were applied. Radiographic and photographic records were available at T0, at the end of protraction (T1) and at least 1 year after bone grafting (T2). Results: Patients with large gaps showed a significant reduction in the bony cleft area and approximation of the soft tissues at T1. All patients received bone grafting with good healing and ossification at T2. Conclusion: In growing patients with UCLP and BCLP with large gaps, presurgical orthodontic protraction seems to be an efficient method to reduce the cleft defect, minimizing the risk of post grafting fistulas, reducing the need for supplementary surgical procedures.